Optimizing Official Letter Management with E-Buddy in Village Government: Optimalisasi Pengelolaan Surat Dinas dengan E-Buddy di Pemerintah Desa - Rahmawati, Riris Dwi; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2024)
Effective management of official letters is crucial for village governance, yet many villages face challenges in this area. Specific Background: Tambak Kalisogo Village in Jabon District, Sidoarjo Regency, implemented the E-Buddy application to address these challenges. Knowledge Gap: While digital solutions like E-Buddy promise efficiency, their practical implementation in village administration is not well-documented. Aims: This study aims to describe and assess the implementation of the E-Buddy application in managing official letters within the Tambak Kalisogo Village Government using a descriptive qualitative method. Results: The study utilized purposive sampling, involving key informants such as the village head, village secretary, and the head of the service section responsible for E-Buddy. Findings indicate that communication within the application was generally effective; however, the transmission was one-directional, focusing solely on communication from the village head to the E-Buddy operator instead of all users. Resource availability, including facilities and infrastructure, was deemed sufficient to support E-Buddy's optimal implementation. However, issues such as margin-setting difficulties and application errors posed challenges. The disposition indicator was aligned with the management of incoming letters, while the bureaucratic structure demonstrated adequate standard operating procedures. Novelty: This study highlights specific implementation challenges, such as margin-setting difficulties and delayed notifications, that need attention from service providers. Implications: The findings suggest the need for improved communication channels and technical support within E-Buddy to enhance official letter management at the village level, with the Sidoarjo Regency Government's support in addressing these obstacles. Highlights: Communication Gap: One-directional communication limits effective use of E-Buddy among village officials. Technical Challenges: Margin-setting and application errors hinder optimal letter management. Resource Adequacy: Sufficient facilities support implementation, but improvements in technical support are needed. Keywords: Village Governance, E-Buddy Application, Official Letter Management, Digital Solutions, Implementation Challenges.